UNCITRAL MODEL LAW ON ELECTRONIC COMMERCE AND MODEL LAW ON ELECTRONIC SIGNATURES - Gunawan Widjaja; Kevin Neil McVey; Jestin Justian; Theresia Vena (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Whereas in analyzing the Model Law on Electronic Commerce and Electronic signatures, the author can see that there is a suggestion that must be conveyed carefully. In this modern era, the Indonesian government needs to review the provisions of its electronic commerce. That although the Model Laws are not a role model for regulations that need to be obeyed absolutely, they are a reflection to fill the legal void or ambiguity in our national law (rechtsvacuum). It is better for the government to continue to fill the void by being given a role model first, which can be used as a spur in producing better e-commerce provision products in the future.